Phonological Variations of Ternate Malay Language - Ety Duwila (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
The people of North Maluku Province speak Ternate Malay, or North Maluku Malay language, as a medium for interethnic communication. This language is a dialect which is an archipelagic variant of the Malay language. Ternate Malay language underwent several phonological, grammatical, and lexical changes as it developed. The purpose of this Phonological Variations of Ternate Malay language study is to characterize the differences in phonological features between Ternate Malay and Standard Malay language (Indonesian). Both synchronic and diachronic research are conducted. The research findings synchronously demonstrate that MSt and MT have distinct linguistic properties. There is no long vowel in MSt, yet there is no [ʙ] sound in MT. Other than that, there are vowel variations and sounds that match both vowels and consonants. Diachronic studies reveal that substitution is a type of cooperative innovation. Assimilation, syncope, apocope, metathesis, prosthesis, lowering of high vowels, and monophthongization are examples of irregular innovations in MSt and MT. Given that MSt continues to use archaic forms, it may be concluded that whereas MT is an innovative dialect, MSt is a conservative dialect based on the retention and innovation forms shown above.